PERAN BIMBINGAN KONSELING KRISTEN DALAM MEMBENTUK KESEHATAN MENTAL DAN KEDEWASAAN IMAN JEMAAT - Esra Renalsi Wijaya; Eurecci; Erlina Paranduk; Dina Limbong; Naomi Putri Tale' (CV. ADIBA ASIHA AMIRA, 2026)
This study aims to examine the role of Christian counseling in shaping the mental health and faith maturity of congregations. The approach used was descriptive qualitative, with data collection techniques through interviews, observations, and documentation studies. The results indicate that Christian counseling plays a significant role in helping congregations overcome psychological stress, manage emotions, and heal emotional wounds through an approach that integrates psychological principles and theological values. Furthermore, counseling also contributes to building a more intimate relationship with God, strengthening self-identity, and developing Christian character that reflects faith maturity. However, counseling services in churches still face challenges such as limited human resources and negative stigmas regarding counseling. Therefore, a development strategy is needed that includes counselor training, congregational education, and the integration of counseling services into church programs. Thus, Christian counseling becomes an effective tool in supporting the holistic growth of congregations.